2019
DOI: 10.1007/s10238-019-00566-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipidome screening in patients with stage I non-small cell lung cancer

Abstract: The ability of early lung cancer diagnosis is an unmet need in clinical practice. Lung cancer metabolomic analyses conducted so far have demonstrated several abnormalities in cancer lipid profile providing a rationale for further study of blood lipidome of the patients. In the present research, we performed a targeted lipidome screening to select molecules that show promise for early lung cancer detection. The study was conducted on serum samples collected from newly diagnosed, stage I non-small cell lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…8 For example, serum levels of lysoPC (C26:0 and C26:1) and PC (C42:4 and C34:4) were different between stage I NSCLC and healthy patients. 22 Some elements and pathways of serum PC and PE profiles increased in patients with lung benign disease and early-stage NSCLC, as compared with healthy, whereas few (e.g., PC 15:0/18:1) significantly elevated in early-stage NSCLC patients alone. 2 It seems that patterns of lipid elements may be associated with the specificity of lung cancer and stage, rather than the intact lipid pathways.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…8 For example, serum levels of lysoPC (C26:0 and C26:1) and PC (C42:4 and C34:4) were different between stage I NSCLC and healthy patients. 22 Some elements and pathways of serum PC and PE profiles increased in patients with lung benign disease and early-stage NSCLC, as compared with healthy, whereas few (e.g., PC 15:0/18:1) significantly elevated in early-stage NSCLC patients alone. 2 It seems that patterns of lipid elements may be associated with the specificity of lung cancer and stage, rather than the intact lipid pathways.…”
Section: Discussionmentioning
confidence: 87%
“…18 In order to face the major challenge that most clinical information was descriptive and unmatched with the digital quantity of omics data, clinical phenomes were scored by DESS and integrated with genomic and proteomic data of patients with acute respiratory distress syndrome and chronic obstructive pulmonary disease. [19][20][21][22] Clinical phenomes were furthermore integrated with lipidomic profiles in patients with pulmonary embolism, acute pneumonia, and acute exacerbation of chronic obstructive pulmonary diseases, based on clinical trans-omics principle. 15 Lipidomic profiles difference between health and lung cancer has been defined and it depends upon methodologies of measurement and analysis, sample preparations and sources, and patient populations and status.…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of them may be mainly due to the increased demand for membrane constituents during malignant transformation, cancer invasion and metastasis. Dysregulation of choline phospholipid metabolism is associated with carcinogenesis and cancer progression, which has been verified in many biomarker studies [26][27][28], including studies of GC [29]. Thus, the abnormal levels of LysoPC and PC may be considered as important biomarkers for GC patients.…”
Section: Discussionmentioning
confidence: 89%
“…levels. Yet another study found that PC levels were elevated in LC patient serum [44]. Such elevated PC levels may be due to an increased need for these membrane phospholipids in cancer cells, given that they are primary components of the cell membrane [45,46].…”
Section: Discussionmentioning
confidence: 98%